2015
DOI: 10.1002/nau.22888
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor muscle training for female stress urinary incontinence: Five years outcomes

Abstract: Although relatively high rates of 5-year adherence to training were demonstrated among our patients, this adherence was not associated with superior treatment outcomes. Further studies are needed to establish the long-term efficacy of PFMT for SUI. Neurourol. Urodynam. 36:132-135, 2017. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…The 12‐month adherence rates reported by women who had been in the CRT were midrange for those included in the 2013 review 7 and comparable with the rates (in younger women) reported for 5‐year adherence in Israel 13 and for older women in Quebec 14 …”
Section: Discussionsupporting
confidence: 64%
“…The 12‐month adherence rates reported by women who had been in the CRT were midrange for those included in the 2013 review 7 and comparable with the rates (in younger women) reported for 5‐year adherence in Israel 13 and for older women in Quebec 14 …”
Section: Discussionsupporting
confidence: 64%
“…In those who are unable to contract the pelvic floor, biofeedback techniques might be useful 90 . Although short-term efficacy is good, with no harmful effects, evidence of long-term benefit is lacking [117][118][119] .…”
Section: Non-surgical Interventionsmentioning
confidence: 99%
“…In those who are unable to contract the pelvic floor, biofeedback techniques might be useful 90 . Although short-term efficacy is good, with no harmful effects, evidence of long-term benefit is lacking [117][118][119] .Incontinence pessaries and intravaginal devices-Women seeking further treatment for stress urinary incontinence who wish to avoid or defer surgery, and are unable to adhere to behavioural therapy, can use vaginal continence pessaries 120 , which aim to compress the urethra. These treatments show the greatest benefit in those with severe stress urinary incontinence 121 .…”
mentioning
confidence: 99%
“…Pelvic floor muscle training (PFMT) is effective and the recommended first-line treatment for women suffering from SUI. [40][41][42] The success rate varies according to the study; selfmotivation is a major dependent factor. 43 The optimal training program is not yet known (frequency, dosage, exercises).…”
Section: Figurementioning
confidence: 99%